-7(3p+2)40=3(5p+6)

Simple and best practice solution for -7(3p+2)40=3(5p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3p+2)40=3(5p+6) equation:


Simplifying
-7(3p + 2) * 40 = 3(5p + 6)

Reorder the terms:
-7(2 + 3p) * 40 = 3(5p + 6)

Reorder the terms for easier multiplication:
-7 * 40(2 + 3p) = 3(5p + 6)

Multiply -7 * 40
-280(2 + 3p) = 3(5p + 6)
(2 * -280 + 3p * -280) = 3(5p + 6)
(-560 + -840p) = 3(5p + 6)

Reorder the terms:
-560 + -840p = 3(6 + 5p)
-560 + -840p = (6 * 3 + 5p * 3)
-560 + -840p = (18 + 15p)

Solving
-560 + -840p = 18 + 15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-15p' to each side of the equation.
-560 + -840p + -15p = 18 + 15p + -15p

Combine like terms: -840p + -15p = -855p
-560 + -855p = 18 + 15p + -15p

Combine like terms: 15p + -15p = 0
-560 + -855p = 18 + 0
-560 + -855p = 18

Add '560' to each side of the equation.
-560 + 560 + -855p = 18 + 560

Combine like terms: -560 + 560 = 0
0 + -855p = 18 + 560
-855p = 18 + 560

Combine like terms: 18 + 560 = 578
-855p = 578

Divide each side by '-855'.
p = -0.6760233918

Simplifying
p = -0.6760233918

See similar equations:

| 18*14*2= | | 5x+32=67 | | N/25-7=-82 | | 3x-2+7+3x-2+7=133 | | -9-5+2-8-9= | | 4x+6+x=180 | | 67y=45n+13 | | 2448/48=x | | X(x-8)=x^2+5x | | 0=40-(1.1xd) | | 49x^2-252x+224=0 | | 42-2x=125 | | 30-5=17+H | | 18(3d)+12d=4884 | | 72x^2=98 | | 3p=10-1 | | -9v-5v-v+7v+5v= | | 3n+8a=144 | | 4+x+8=-48 | | 30+15=2x+4 | | 8n+3a=144 | | 9/3.14= | | 6x-9=4x+4 | | .432=logx^2 | | .20/50 | | 3*7/6 | | (y-5)(-3y^2+6y+3)=0 | | 2x+4+3x=2x+3 | | 40+40y-16=13y-12-3y | | 36=3.14(4)h | | 7x-2y=-26 | | 5g+4(-5+3g)=11g |

Equations solver categories